ELEMENTARY SCHOOL STUDENTS' PERCEPTION OF INTERACTIVE LECTURE METHOD IN ENGLISH TEACHING IN ASAHAN - Sahmiral Amri Rajagukguk; Diah Safithri Armin, Anggun Siska Pratiwi (Indonesian Journal of Education (INJOE), 2024)
This study examines elementary school students' perceptions of the interactive lecture method of teaching English in SDN 015860 Rawang Baru, Asahan. The background of this study is the need for more effective and engaging teaching methods compared to conventional methods, which often lack active student participation. The purpose of this study was to explore how students experienced the interactive lecture method and its impact on their understanding of English. Qualitative methods were used, with data collected through interviews with eight pre-selected students. The findings showed that students responded positively to the method, felt more motivated, learned faster and found English easier to understand. The implications of this study suggest further development in the application of this method in the elementary school curriculum, especially in rural areas.